Complex Design by Simple Robots: A Collective Embodied Intelligence Approach to Construction. (July 2017) - Petersen, Kirstin; Nagpal, Radhika
Abstract : Nature's builders – from termites to beavers – offer a model of collective intelligence that can inspire robotic construction. Kirstin Petersen, Assistant Professor in Electrical and Computer Engineering at Cornell University, Ithaca, New York, and Radhika Nagpal, Professor in Computer Science at the Harvard School of Engineering and Applied Sciences, Cambridge, Massachusetts, describe several recent projects in this field that they have been involved in, both separately and collaboratively.